RIG-I Enhances Interferon-α Response by Promoting Antiviral Protein Expression in Patients with Chronic Hepatitis B. Issue 7 (October 2018) - Wu, Shu; Lin, Jinpiao; Fu, Ya; Ou, Qishui
Background: Interferon (IFN)-α is widely used for the treatment of chronic hepatitis B (CHB) infection due to the high rate of hepatitis B surface antigen (HBsAg) seroconversion. However, IFN-α treatment has a number of side effects. Thus, identification of molecular biomarkers to predict IFN-α therapeutic effect would be useful in the clinic. In this study, we aimed to investigate the role of retinoic acid-inducible gene-I (RIG-I) in prediction of IFN-α curative effect of CHB patients. Methods: A total of 65 CHB patients treated with pegylated IFN-α weekly for 48 weeks were enrolled. Realtime PCR was performed for detection of RIG-I and IFN-stimulated gene (ISG) expression. In vitro, the HepG2 cells were transfected with siRNA and levels of RIG-I and anti-HBV proteins were detected by western blot. The P -values were calculated in SPSS 18.0. The statistical significance level was accepted as P <0.05. Results: In this study, we found RIG-I expression in peripheral blood mononuclear cells was higher in responder than non-responder CHB patients treated with IFN-α therapy. In HBV-transfected HepG2 and Huh7 cells, RIG-I enhanced IFN-α response by promoting anti-HBV protein expression such as double-stranded RNA-dependent protein kinase (PKR), oligoadenylate synthetase (OAS), adenosine deaminase (ADAR1) and Mx protein. Knocking down of RIG-I could downregulate the expression of these proteins. Inhibited RIG-I expression by RIG-I siRNA deceased STAT1 phosphorylation. Conclusions: Our results revealed RIG-I enhanced IFN-α response by promoting antiviral protein expression via the STAT1 pathway. RIG-I may be a new predictive factor for prediction of IFN-α efficacy in CHB patients.